Compliance of water recycling schemes in Western Australia: an analysis of water recycling from 2003 to 2009 - Shishkina, N.; Hannelly, Toni; Rodriguez, C. (Australian Water Association, 2013)
Water recycling schemes have been in operation in Western Australia since 1960. Periodic microbial water quality monitoring has been in place to demonstrate fit-for-purpose recycled water as part of the regulatory framework for wastewater reuse. This study analysed the compliance of water recycling schemes in the Department of Health database over a seven-year period (2003-2009). The original intention was to analyse the compliance of all 92 schemes in the database; however it was necessary to exclude 21 schemes because they either lacked sufficient data or their recording standards were too inconsistent for the analysis. Compliance was analysed by comparing: i) the observed microbial results against the quality criteria; and ii) the number of samples analysed against the expected number of samples based on regulatory frequency requirements. The results indicate that 12% of the 71 schemes analysed did not comply with water quality criteria over the seven-year period and most of the original 92 recycling schemes did not comply with the expected number of samples. Challenges faced by existing schemes in conforming to the Australian Guidelines for Water Recycling: Managing Health and Environmental Risks (Phase 1) (2006) and the Guidelines for the Non-Potable Uses of Recycled Water in Western Australia (2011) are discussed.